Macrohabitat Composition Surrounding Successful and Depredated Northern Bobwhite Nests - Eric L. Staller; William E. Palmer; John P. Carroll (National Quail Symposium Proceedings, 2017)
Relationships among macrohabitat and depredation of northern bobwhite (Colinus virginianus) nests are poorly understood. Yet, macrohabitat composition may influence the nest predator community and, therefore, the vulnerability of northern bobwhite nests to depredation. We determined if macrohabitat composition surrounding bobwhite nests influenced nest placement, nest success, and which predators were responsible for depredating nests. We characterized macrohabitats at 2 scales, 8 and 16 ha, by surrounding both bobwhite nests, and an equal number of random locations, with a circular buffer. Random points were placed within the area used by bobwhites on our study area. We then determined the acreage of each macrohabitat category within each circular buffer to determine the macrohabitat composition. Macrohabitat categories included hardwood forested drains, upland pine forests burned in March of the same calendar year, upland pine forests burned in March of the previous calendar year, and fields. We documented nest predators using infrared video cameras placed at the nest site. We monitored 104 bobwhite nests on Tall Timbers Research Station (TTRS) during 1999 and 2000. Size of the circular buffer around nests did not qualitatively affect results. Area (ha) of upland pine forests and fields were similar at depredated nests, hatched nests, and random locations. However, there was an average of 81% and 56% more area of hardwood drain in the circular buffers associated with random locations than at successful and depredated nests, respectively. Area of upland pine forests and fields were similar for nests depredated by raccoon (Procyon lotor), armadillo (Dasypus novemcinctus) and snake (Elaphus spp.). However, there was an average of 6.1 and 3.3 times more area of hardwood drain surrounding nests that were depredated by snakes relative to nests depredated by raccoons and armadillos, respectively. While our sample sizes were low, bobwhites exhibited a tendency to place nests in landscapes with less hardwood drain than were generally available on the study area. Macrohabitat surrounding nests influenced the type of nest predator to depredate nests. To minimize depredation of bobwhite nests by snakes, we suggest nesting cover should be developed away from drain edges.
Keywords: Colinus virginianus; macrohabitat; nest predators; nesting success; northern bobwhite; Tall Timbers Research Station; video